Core Curriculum Focus of Educational Foundation Across the Continents - Catipay, Elen; Tamban, Gellie; Galigao, Regina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the core curriculum focus of educational foundations across continents, with emphasis on identifying both common and distinct curriculum variables found in global education systems. Specifically, it aimed to determine shared curriculum priorities such as literacy, numeracy, STEM, and technology, while also analyzing region-specific emphases including moral education in Asia, vocational pathways in Europe, Early Childhood Care and Education and Global Citizenship Education in South America, social studies in North America, and recreation and creativity in Africa. The study was anchored on Comparative Education Theory, curriculum contextualization, global citizenship education, and educational benchmarking, which provided the basis for analyzing how global curriculum directions are adapted within different cultural, social, and educational contexts. A qualitative comparative research design supported by data mining techniques was used. Since the study relied on secondary data, there were no human respondents; instead, data were gathered from international educational reports, curriculum frameworks, academic literature, and policy documents. Keywords such as literacy, numeracy, STEM, technology, moral education, Early Childhood Care and Development/Early Childhood Care and Education, global citizenship, social studies, and creativity were used to identify, filter, and classify relevant information across continents. The data were analyzed through data mining procedures and qualitative thematic analysis to determine recurring patterns, common curriculum foundations, and distinct regional priorities. He findings revealed that literacy, numeracy, STEM, and technology are consistently emphasized across continents as universal pillars of education. These areas support foundational knowledge, cognitive development, digital competence, critical thinking, academic success, workforce readiness, and participation in a rapidly changing society. However, the study also found that curriculum implementation varies according to regional needs, cultural values, socio-economic conditions, historical contexts, and development priorities. Asia emphasizes moral education, values formation, discipline, and social harmony; Europe focuses on vocational pathways, economic competitiveness, and school-to-work transition; South America highlights Early Childhood Care and Education and Global Citizenship Education; North America prioritizes social studies, civic competence, and democratic participation; while Africa promotes recreation, creativity, cultural identity, and holistic education. The study concluded that global education systems reflect a dual process of standardizing essential competencies while contextualizing curriculum content to remain locally relevant. It recommended stronger curriculum alignment between global competencies and local contexts, interdisciplinary integration of core learning areas, support for region-specific curriculum innovations, teacher training, equitable access to educational technology, and further comparative curriculum research. The study is naturally aligned with SDG 4 – Quality Education because it focuses on curriculum relevance, foundational learning, digital literacy, teacher capacity, and inclusive educational development. It also connects with SDG 8 – Decent Work and Economic Growth, SDG 9 – Industry, Innovation and Infrastructure, SDG 16 – Peace, Justice, and Strong Institutions, and SDG 17 – Partnerships for the Goals through its emphasis on workforce readiness, technological learning, civic responsibility, and global educational cooperation. Its sustainability impact lies mainly in educational, institutional, social, cultural, technological, and socio-economic sustainability by supporting curricula that are globally informed, locally responsive, inclusive, and relevant to diverse learners and communities.